Introduction to nuclear techniques in agronomy and plant biology a volume in Pergamon International Library of Science, Technology, Engineering and Social Studies - Vose, Peter B. (Pergamon international library of science, technology, engineering, and social studies, 1980)
Introduction to Nuclear Techniques in Agronomy and Plant Biology is a 15-chapter book that begins with an explanation of the nature of isotopes and radiation, nuclear reactions, and radioisotopes. Subsequent chapters describe the radioassay, use of stable isotopes as tracers, and activation analysis for biological samples. Other chapters discuss X-ray fluorescence spectrography for plants and soils; autoradiography; isotopes in soils studies; isotopic tracers in field experimentation; and nuclear techniques in plant science and soil water. The last chapter centers on the radiation and other induced mutations in plant breeding.--Provided by publisher.